2008
DOI: 10.1016/j.adolescence.2008.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The developmental pattern of resistance to peer influence in adolescence: Will the teenager ever be able to resist?

Abstract: Common folklore seems to suggest that adolescents are particularly susceptible to peer influence. However, from the literature the exact age differences in susceptibility to peer influence remain unclear. The current study's main focus was to chart the development of general susceptibility to peer pressure in a community sample of 10–18 year olds (N = 464) with the recently developed Resistance to Peer Influence Scale (RPI). The one‐factor structure of the RPI was cross‐validated in the present sample, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
194
10
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(232 citation statements)
references
References 37 publications
17
194
10
11
Order By: Relevance
“…As a result, we cannot draw conclusions from the current study about whether the results are unique to prosocial behaviour (although studies indicate that age‐related decreases in social influence are seen for other types of behaviour too, such as risk perception and antisocial behaviour; Knoll et al., 2015, 2017; Steinberg & Monahan, 2007; Sumter et al., 2009). Further studies could assess how age affects prosocial, neutral and antisocial influence within the same paradigm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, we cannot draw conclusions from the current study about whether the results are unique to prosocial behaviour (although studies indicate that age‐related decreases in social influence are seen for other types of behaviour too, such as risk perception and antisocial behaviour; Knoll et al., 2015, 2017; Steinberg & Monahan, 2007; Sumter et al., 2009). Further studies could assess how age affects prosocial, neutral and antisocial influence within the same paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that susceptibility to social influence is at its highest in late childhood (approximately age 8–10 years) then gradually decreases across the adolescent years (approximately 11–18 years) and into adulthood (19 years and above; Knoll, Leung, Foulkes, & Blakemore, 2017; Knoll, Magis‐Weinberg, Speekenbrink, & Blakemore, 2015; Steinberg & Monahan, 2007; Sumter, Bokhorst, Steinberg, & Westenberg, 2009). As such, relative to adults, children and adolescents are particularly susceptible to being influenced by others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, most of the studies finding a male tendency to experience peer pressure used self-report measures focused on delinquency, misconduct and substance use (e.g., Berndt 1979;Bradley and Wildman 2002;Crockett et al 2006;Duangpatra et al 2009;Dumas et al 2012). However, other studies showing this pattern of male-proneness used self-report measures that assessed broader experiences of peer pressure (Goldstein et al 2005;Iwamoto and Smiler 2013;Steinberg and Monahan 2007;Sumter et al 2009). Such inconsistencies in the tools used to assess susceptibility to deviant peer pressure complicate findings and make it challenging to determine whether there are reliable gender differences.…”
Section: Measurement Of Peer Pressurementioning
confidence: 99%
“…The theory of planned behavior (Ajzen, 1991) states that behavior is determined by the intention to execute this behavior, which is, in turn, determined by the social norm -described as the social pressure people experience to behave in a particular way -, the perceived behavioral control and the attitude toward the behavior. Following this theory and the fact that teenagers are particularly sensitive to peer pressure (Sumter, Bokhorst, Steinberg, & Westenberg, 2009), it could be hypothesized that the 'social norm' can have an important impact on pupils' behavior. Because of the opportunities SNSs offer when sharing information -e.g., communicating (Pruulmann-Vengerfeldt & Runnel, 2012) and creating an online identity (Hum et al, 2011;Madden & Smith, 2010) -risky behavior could be stimulated between peers and peer pressure could prevent behavioral change after the intervention.…”
Section: First Revision Of Materialsmentioning
confidence: 99%